LEARNHIV: development and validation of a mobile application for primary health care nurses focused on HIV care/prevention - Melyane de Assunção Gaia; Eliã Pinheiro Botelho; Glenda Roberta Oliveira Naiff Ferreira; Cintia Yolette Urbano Pauxis Aben-Athar; Andressa Tavares Parente; Fabianne de Jesus Dias de Sousa; Marielna Silva dos Santos; Natalia Maria Vieira Pereira-Caldeira; Richardson Augusto Rosendo da Silva; Aline Maria Pereira Cruz Ramos (BMC, 2023)
Abstract Introduction Human immunodeficiency virus (HIV) infection is a relevant public health problem is worldwide. From the change in the health care of people living with HIV (PLHIV) in Primary Health Care (PHC), nurses gained autonomy in their workflow, which requires a significant technological arsenal for the planning, organization and functioning of services. It is believed that the development of a mobile application for the care/prevention of HIV will contribute to the strengthening of care, resulting in greater autonomy and empowerment of nurses in Primary Health Care. Objective To develop and validate a content script for a mobile application for nurses in PHC containing information about PLHIV management/care in PHC. Methods This is a methodological study developed in three phases: exploratory study, content elaboration process and validation by the 16 judges. Results The application was evaluated and validated satisfactorily in terms of content and appearance, with an average Content Validity Index (CVI) of 0.99 (99%), Item Content Validity Index (I-CVI) and Medium Content Validity (S-IVC/AVE) also obtained satisfactory levels. Conclusions The construction of the prototype of an application called LearnHIV, is considered a valid instrument in terms of content and appearance, according to the judges. Trial registration None because it is not an intervention study.